PŪJĀ TRISANDHYĀ DI DESA ADAT TONJA KECAMATAN DENPASAR UTARA KOTA DENPASAR - Tuty Setiarsih, Dewa Ayu Putu; I Ketut Donder; I Gusti Made Widya Sena (Pangkaja: Jurnal Agama Hindu, 2024)
The concept of worship is a very important aspect for every religious community. The way of prayer for Hindus in Indonesia is guided by performing Pūjā Trisandhyā in order to know and feel or recognize the qualities and omnipotence of God in accordance with their beliefs and beliefs. Pūjā Trisandhyā belongs to upasana and is the path of bhakti yoga. The Pūjā Trisandhyā Mantra is only chanted through loudspeakers, without any effort to provide education regarding a deep understanding of it. The aim of this research is to enrich Trisandhyā's review and explore phenomena related to the implementation of Pūjā. The method used in this research is a qualitative method with a philosophical and phenomenological approach. The results of this research show that the implementation of Pūjā Trisandhyā in the Tonja Traditional Village tends to be seen as a normal thing that must be practiced tocomplete the prayers in a piodalan ritual. If it is not carried out three times in accordance with the time requirements, some people feel that this is not/is not a problem, the implementation of the puja has been replaced with other activities; such as mebanten canang, praying silently, ngayah in the banjar for joy and sorrow activities, working to earn a living and so on. Keywords: Pūjā Trisandhyā; Desa Adat Tonja